An Investigation into Undergraduate Students’ Perception of Kahoot Mediated E-Assessment - Moh. Arif Mahbub (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
This study is an endeavor to depict undergraduate students’ perception of a digital game-based learning (DGBL) platform called Kahoot! integrated into the undergraduate students’ learning. To this end, a sequential explanatory study was employed. Undergraduate students from a private university in Indonesia (N=21) agreed to participate in this study. A web-based five-point Likert scale questionnaire was developed to examine their perceptions of this platform. A focus-group interview was also conducted to detect their in-depth feelings. The results indicated that they positively appreciated the integration of this tool into classroom instructions. Implications, conclusion and limitations were then discussed.